Fetomaternal Outcome in Pregnancy with Hepatitis E Infection (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Hepatitis E; pregnancy; fulminant hepatic failure; maternal mortality; still births; hepatic encephalopathy; coagulopathy